2000
DOI: 10.1677/joe.0.1660553
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of human insulin-like growth factor-binding protein 3 gene inhibits cell growth and tumorigenicity: a cell culture model for lung cancer

Abstract: IGF-I and IGF-II are potent mitogens, postulated to exert autocrine/paracrine effects on growth regulation in human lung cancer. Their proliferative effects are modulated by IGF-binding proteins (IGFBPs), which are found in conditioned medium (CM) of lung cancer cell lines. The biological role of the IGFBPs, which are ontogenetically and hormonally regulated, is not fully understood. Both inhibitory and stimulatory effects on cell growth have been demonstrated. Exogenous IGFBP-3 has been consistently shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…For example, in vitro data indicate that the inhibitory effects of IGFBP-3 are likely due to both its sequestration of IGF-I and IGF-Iindependent effects; specifically, IGFBP-3 can bind proteins involved in cell cycle in the nucleus (21) and has antiproliferative (22)(23)(24) and direct proapoptotic activities (25)(26)(27)(28). Thus, high IGFBP-3 levels could lead to less replication and/or greater loss of oncogenic HPV infected cells (that is, to levels below the threshold of detection).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vitro data indicate that the inhibitory effects of IGFBP-3 are likely due to both its sequestration of IGF-I and IGF-Iindependent effects; specifically, IGFBP-3 can bind proteins involved in cell cycle in the nucleus (21) and has antiproliferative (22)(23)(24) and direct proapoptotic activities (25)(26)(27)(28). Thus, high IGFBP-3 levels could lead to less replication and/or greater loss of oncogenic HPV infected cells (that is, to levels below the threshold of detection).…”
Section: Discussionmentioning
confidence: 99%
“…Several independent reports showed that IGFBP-3 has potent antitumor activities in vitro and in vivo (43,44). A prospective study also showed that IGFBP-3 was inversely associated with prostate cancer risk (45).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous overexpression of IGFBP-3 has been shown to significantly reduce tumor formation against human non-small-cell lung cancer and prostate xenografts (34,35). Delivery of IGFBP-3 into H1299 nonsmall-cell lung cancer xenografts via a recombinant adenovirus reduced tumor volume (36).…”
Section: Discussionmentioning
confidence: 99%